Hugo Grotius in International Thought - Jeffery, R. author. aut Link
VIII, 216 p.
Keywords: Drawing on the development of 'Grotian' scholarship in international legal and political thought, this book seeks to ascertain precisely what the term has meant, both historically and as it is employed in contemporary scholarship.